The Status of Social Sciences and Globalization - Gylys, Povilas (Ekonomika, 2005)
Globalization and evolving knowledge society are the major fundamental challenge to the social science. Diversification of social life on the all levels of reality - individual, family, community, state, mankind - opens new opportunities and give birth to the new threats. To grasp these two - positive and negative - sides of our life the more precise, relevant cognitive means are needed. Better conceptualized, free of ideological and political influences, cleaned from elements of common sense, conventional wisdom social knowledge would better conform to the requirements of “pure” science and would become more reliable source of viable, effective policies pursued by national states and international organizations. One of preconditions of the success of social science is the settlement of old paradigmatic competition between methodological individualism and methodological holism. Both have mooted historical records. Soviet experiment was based mainly on holistic assumptions; market fundamentalism is the natural outcome (product) of individualistic thinking. Methodological (metatheorical) exploration of all these problems faced by social sciences, though costly they are, would give better cognitive perspective to them, would “harden” them. Having said this we would like to stress that social sciences will never achieve the level of ”hardness” attributed to natural sciences and first of all physics. Social sciences explore social reality which is qualitatively differs from non-living world. The latter is much more weakly structured, less deterministic, pulsating, the link between action and response is not linear etc. The quality social knowledge is a public good, which can contribute substantially to the social progress. Unfortunately in the framework of individualistic thinking the notion of public good is marginalized and knowledge is not treated as economic resource. Author of this article join those researchers who argue for holistic perception of social reality which provides better, wider understanding of modern world and thereby provides more solid foundation for relevant state and global policies.